2015
DOI: 10.1111/fcsr.12113
|View full text |Cite
|
Sign up to set email alerts
|

Family Educators’ Technology Use and Factors Influencing Technology Acceptance Attitudes

Abstract: The purpose of the study was to examine family educators’ use of information and communication technology and factors that predict attitudes favorable to the adoption of technology in practice. Data were obtained from 210 family educators in the United States. Structural equation modeling tested the validity of an adapted Technology Acceptance Model to predict influences on attitudes. Descriptive statistics showed that Internet searching and cell phones were predominantly used both at work and for personal use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 27 publications
9
22
0
Order By: Relevance
“…The result is also similar to previous research which shows that perceived usefulness positively affects attitude toward technologies (Masrom, 2007;Page, 2015;Walker & Kim, 2015). Perceived usefulness (ID) of wearable trackers positively affected attitude toward using (D) wearable trackers (b = .518, p ≤ .001, R 2 -adjusted = 0.436).…”
Section: Simple and Multiple Linear Regression Analysis Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The result is also similar to previous research which shows that perceived usefulness positively affects attitude toward technologies (Masrom, 2007;Page, 2015;Walker & Kim, 2015). Perceived usefulness (ID) of wearable trackers positively affected attitude toward using (D) wearable trackers (b = .518, p ≤ .001, R 2 -adjusted = 0.436).…”
Section: Simple and Multiple Linear Regression Analysis Resultssupporting
confidence: 90%
“…This result is similar to other studies on technology acceptance attitudes (Masrom, 2007;Page, 2015;Walker & Kim, 2015). The perceived ease of using (ID) wearable trackers (b = .453, p ≤ .001, R 2 -adjusted = 0.436) positively affected attitude toward using (D) the wearable trackers.…”
Section: Simple and Multiple Linear Regression Analysis Resultssupporting
confidence: 89%
“…An adaptation to the model considers external influences on technology attitudes and use such as the availability and quality of training that could affect the perception of comfort with technology or being surrounded by peers whose assessment could affect the perception of the usefulness of the technology. Walker and Kim () utilized an adapted TAM (Teo, Lee, & Chai, ) with a national sample of nonformal family educators and concluded that facilitating conditions and subjective norms indirectly influenced technology attitudes. Walker and Kim () found that subjective norms influenced attitudes as mediated by Perceived Usefulness (PU) and Perceived Ease of Use (PE) and that facilitating conditions influenced attitudes mediated by Perceived Ease of Use (PE).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Walker and Kim () utilized an adapted TAM (Teo, Lee, & Chai, ) with a national sample of nonformal family educators and concluded that facilitating conditions and subjective norms indirectly influenced technology attitudes. Walker and Kim () found that subjective norms influenced attitudes as mediated by Perceived Usefulness (PU) and Perceived Ease of Use (PE) and that facilitating conditions influenced attitudes mediated by Perceived Ease of Use (PE). Their study suggested that training and assistance viewed as relevant to family education practice, and the exposure to peers who were supportive of technology use positively influenced the attitudes of the professional.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation